EFISIENSI DAN SALURAN PEMASARAN SAYURAN DI KOMUNITAS HIDROPONIK SOLORAYA - Rosita Dewati; Muhammad Fathul Anwar; Yos Wahyu Harinta (Agros Journal of Agriculture Science, 2023)
Hydroponics is an alternative to plant cultivation due to limited land ownership by farmers. The results of hydroponic plants have many benefits desired by consumers such as product quality, taste and color as well as guarantees of hygiene. The Solo area has a hydroponic community, namely the Greater Solo Hydroponic Community (Kohisora). The resulting product is fresh vegetables which are sold through a variety of ways and marketing distribution channels. This study aims to determine the efficiency and marketing channels of vegetables in the Kohisora hydroponic community. The data used is primary data. The sample used in this study was 45 people consisting of 15 hydroponic vegetable producers of Kohisora who had sold their products through various marketing channels, 5 traders and 25 consumers who bought hydroponic vegetables. Data analysis uses marketing margin and marketing channel analysis. Based on the research results, it is known that the marketing channel for Kohisora vegetable products is still efficient. It is recorded that the marketing efficiency rate that occurs in vegetable shops/kiosks is still below 50%. Each of the marketing efficiency figures for each type of vegetables starting from mustard greens, lettuce and pakcoy in vegetable shops/kiosks has an indicator value of 18.1%; 16.6%, and 25%. This is the same as the marketing channels that occur in supermarkets which are still relatively efficient. Each marketing efficiency score for each type of vegetable starting from mustard greens, lettuce and pakcoy in vegetable stores/kiosks has an indicator value of 25%; 28.5% and 31.8%.Hidroponik menjadi salah satu alternatif budidaya tanaman akibat keterbatasan kepemilikan lahan petani. Hasil tanaman hidroponik memiliki banyak manfaat yang diinginkan oleh konsumen seperti mutu produk, rasa, dan warna serta jaminan higienitas. Wilayah Solo memiliki komunitas hidroponik yaitu Komunitas Hidroponik Solo Raya (Kohisora). Produk yang dihasilkan adalah sayuran segar yang dijual melalui berbagai macam cara dan saluran distribusi pemasaran. Penelitian ini bertujuan untuk mengetahui efisiensi dan saluran pemasaran sayuran di komunitas hidroponik Kohisora. Data yang digunakan adalah data primer. Sampel yang digunakan pada penelitian sejumlah 45 orang terdiri dari  15 produsen sayuran hidroponik Kohisora yang pernah melakukan penjualan produk melaui berbagai macam saluran pemasaran, 5 pedagang dan 25 orang konsumen yang membeli sayuran hidroponik. Analisis data menggunakan analisis margin pemasaran dan saluran pemasaran. Berdasarkan hasil penelitian diketahui bahwa saluran pemasaran produk sayuran Kohisora masih efisien. Tercatat angka efisiensi pemasaran yang terjadi di toko/kios sayuran masih di bawah 50%. Masing-masing angka efisiensi pemasaran pada setiap jenis sayuran dimulai dari sawi, selada dan pakcoy di toko/kios sayur memiliki indikator nilai 18,1% ; 16,6%, dan 25%. Hal ini sama dengan saluran pemasaran yang terjadi di supermarket yang masih terbilang efisien. Masing-masing angka efisiensi pemasaran pada setiap jenis sayuran dimulai dari sawi, selada dan pakcoy di toko/kios sayur memiliki indikator nilai 25% ; 28,5% dan 31,8%.